The effects of dexmedetomidine on renal injury induced by intra-abdominal hypertension in rats - Yaman, Ferda; Boybeyi, Özlem; Köse, Emine Arzu; Balcı, Mahi; Kısa, Üçler; Apan, Alpaslan (Scientific Publishers of India, 2016)
Introduction: Intra-abdominal hypertension (IAH) and abdominal compartment syndrome (ACS) are potentially life-threatening conditions in critically ill patients. Laparascopic surgery is the gold standard and has been widely performed for many procedures since its inception in the early 1980s. Pneumoperitoneum is essential for laparascopic surgery. Dexmedetomidine is a potent and highly selective ?-2 adrenoceptor agonist with sympatholytic, sedative, amnestic and analgesic properties without respiratory depression. There is increasing evidence of its organ protective effects against ischemic and hypoxic injury, including neuroprotection, cardioprotection and renoprotection. The aim of this experimental study was to investigate the effects of the ?-2 adrenoceptor agonist, dexmedetomidine on IAH induced by renal injury. Materials and methods: A total of 24 male Wistar-albino rats were randomly separated into 4 groups as the control group (CG, n=6), sham group (SG, n=6), low-dose group (DXLD, n=6) and high-dose group (DXHD, n=6). In CG, no intervention was made. IAH was obtained by insufflating atmospheric air with percutaneous intraperitoneal needle using a manual insufflator of manometer up to 15 mmHg. At the 60th min, in SG, 1.5 ml/100 gr/hr saline was infused. In DXLD, 0.5 µg/kg/hr, and in DXHD, 1 µg/kg/hr dexmedetomidine (Precedex, 100 µg/ml; Abbott, Istanbul, Turkey) was infused intravenously. At the 90th min, a midline incision was made and the left kidney was harvested by median laparatomy for the measurement of tissue nitric oxide (NO), malondialdehyde (MDA) level and histopathological examination for proximal tubule injury by light microscopy. Results: No significant difference was determined between the groups either biochemically or histopathologically (p>0.05). Conclusion: Dexmedetomidine may not provide renoprotective effects within the clinical infusion doses of 0.5 µg/kg/hr, and 1 µg/kg/hr.
Keywords: Dexmedetomidine; Intra-Abdominal Pressure; Renal Injury